Dieta e compotamento de forrageio de duas espécies de Tropidurus (Squamata,Tropiduridae) em uma área de Caatinga do Nordeste do Brasil - Kolodiuk, Miguel Fernandes (2008)
Tropidurus semitaeniatus and Tropidurus hispidus are lizard species that are widely distributed in Brazil. The former is endemic to the Caatingas, where they live in syntopy with the latter, which is distributed in other ecosystems and biomes. In this work, diet was evaluated including seasonal variations as well as foraging behavior, to determine the importance of these factors in the structure of these populations and the coexistence of these species in syntopy. No significant difference was found in diet composition between the two species, although T. hispidus feed on larger preys than do T. semitaeniatus; this fact, along with the different foraging behavior in the rainy season, are ecological factors that contribute to the syntopic coexistence of these species in the Caatinga area studied